Cultural contents of senior high school English textbook entitled “Bahasa Inggris” - Dwinda Dwi Lestari; Surono; Suciwati Ika (Universitas Ahmad Dahlan, 2022)
One of the most important aspects that must be included in ELT textbooks is culture. This research aims at exploring types of cultural contents and cultural elements. The subject of this research was English Textbook for grade XII entitled “Bahasa Inggris”. This research belongs to content analysis. Document observation was used to collect the data which were analyzed by using Miles & Huberman’s model and coding method. The research findings show that there were three types of culture found in this textbook, namely the source culture (66 times or 58%), target culture (34 times or 30%), and, international culture (14 times or 12%). Concerning the cultural elements, they were represented by product (39 times or 80%), person (9 times or 18%), and practice (1 times or 2%). Meanwhile, perspective was not represented. It implies that the textbook still focused on source cultures which were more easily internalized by the learners and on products which were the most concrete for learners to learn the culture. It is recommended that the authors of the textbook balance the cultural contents proportionally and the teachers creatively insert more target and international cultures to avoid cultural shocks.